Politicization of accounting / Halil Paino - Paino, Halil (Universiti Teknologi MARA Cawangan Pahang, 2002)
The figures that accountants report either in financial statements or published annual reports will give significant effect on economics behavior, have impact on budgeting process and attract public and parliamentary interest. Accounting rules therefore affect human behavior. Hence, the process by which they are made is said to be political. This article is addressing the issues of political impact in accounting.